Dissolution profile evaluation of solid pharmaceutical forms containing chloramphenicol marketed in Brazil - Ferraz, Humberto Gomes (2007)
The dissolution profile for solid pharmaceutical forms containing chloramphenicol 250 mg available in Brazil was determined using a method from the American Pharmacopoeia (United States Pharmacopoeia, 2004) and then compared. Two different methods of dissolution profile comparison were used: ANOVA, and an independent model. Differences between the formulations were reflected in the dissolution profiles. The presence of metastable polymorphs or amorphous forms of chloramphenicol palmitate might be responsible for variations in the concentration of the drug observed within formulations.